АКТИВНОСТИТЕ НА МАКЕДОНСКОТО ГРАЃАНСТВОТО И ИНТЕЛИГЕНЦИЈА НА ЦРКОВЕН И ПРОСВЕТНО-КУЛТУРЕН ПЛАН (ПРЕД И ПО БЕРЛИНСКИОТ КОНГРЕС) (Philological Studies, 2019)
In the 1860s and 1870s the Macedonian middle class and the parish education councils in the almost all Macedonian town and bigger villages refused obedience to the Patriarchate of the Constantinople and the archpriests in Macedonia. This included rejection to pay the church taxes to the Patriarchate and its bishops and to mention the name of the Patriarch as well as names of the bishops of the eparchies. In a great number of the Macedonian towns and bigger villages the nationally conscious middle class, intelligentsia and rich villagers took control of the existing parishes. With the early 80s of the 19th century will appear new forms of the movement against denationalization policy of the neighboring states.
Keywords: Macedonia, citizenship, intelligentsia, parish educational councils, cities, education, culture, companies